KUTTAB: MADRASAH PADA MASA AWAL (UMAYYAH) PENDIDIKAN ISLAM - Fahruddin, M. Mukhlis (Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2010)
Kuttab is fist Islamic education institute, the learning is simple system; reading, writing, physical exercise and skill. This institute development potency with Islamic character. The curriculum balanced intellectuality and spirituality. This article gives information about the firs institute education and scientific tradition in Islam. This tradition will hope motivator and innovator to development Islamic education in Indonesia. This article analyses intellectual tradition in Umayyah. The objective of the analyses awakens our awareness of intellectual tradition, because it will lead our nation into a better future.Â Creating such condition requires the involvement of each component of this nationKey word: Kuttab, Madrasah, Pendidikan Islam, Anak